82.3k views
0 votes
6(w-1)=3(3w+5)(if there is no solution,type in ''no solution)w= Answer

2 Answers

2 votes

Answer:

3

Explanation:

multiply the no. in the brackets

6w-6=9w+15

collect like terms

9w-6w=15-6

3w=9

divide both sides by 3w

3w/3 = 9/3

w=3

User Shadesfear
by
5.3k points
5 votes

Answer:

the answer is "w = -7"

Explanation:

6*(w-1) = 3*(3*w + 5)

--> 6*w - 6 = 9*w + 15

--> 9 * w - 6 * w = -6 -15

--> 3 * w = -21

--> w = -21 / 3

--> w = -7

User CaNNaDaRk
by
5.5k points